Impaired topographic organization in cognitively unimpaired drug-naïve patients with rigidity-dominant Parkinson's disease. (November 2018) - Hou, Yanbing; Wei, Qianqian; Ou, Ruwei; Yang, Jing; Song, Wei; Gong, Qiyong; Shang, Huifang
Abstract: Background: Resting-state functional magnetic resonance imaging (fMRI) and graph theory approaches have been combined to investigate the topographic organization in Parkinson's disease (PD). Method: Twenty cognitively unimpaired drug-naïve patients with rigidity-dominant PD (PDAR ) and 20 age-, sex-, and education-matched healthy controls were included. Small-world profile and topographic properties (clustering coefficient ( C p ), characteristic path length ( L p ), local efficiency ( E loc ), global efficiency ( E glob ), nodal efficiency ( E nod ), nodal degree ( N Deg ), and nodal betweenness ( N Bet )) were measured and compared between two groups, with age, gender and education as covariates. Correlation analyses between topographic features and the unified PD rating scale part-III (UPDRS-III) scores, cognitive scores were performed. Results: PDAR patients presented the small-world property, and abnormalities at the nodal level ( E nod, N Deg, and N Bet ) but not at the global level ( C p, L p, E loc, and E glob ). Our results revealed lower nodal centralities mainly in the occipital lobe and areas of the limbic system (including amygdala nucleus), and higher nodal centralities in distributed frontal and temporal regions. Notably, the decreased nodal efficiency of occipital regions (including the calcarine area, lingual area and superior occipital gyrus (SOG)) was negatively correlated with UPDRS-III scores. And the nodal efficiency of the calcarine area was positively correlated with visuospatial scores. Conclusion: Our results may provide insights into the underlying pathophysiology of PDAR and aid the development of potential biomarkers of the disease progression and cognitive decline in PDAR patients. Highlights: PDAR patients presented the small-world property. PDAR patients showed abnormalities at the nodal level, but not at the global level. The topographic disruption of occipital regions was valuable in PDAR . Our results may aid the development of new biomarkers in PDAR patients.